2007
DOI: 10.1104/pp.107.101436
|View full text |Cite
|
Sign up to set email alerts
|

Double Mutants Deficient in Cytosolic and Thylakoid Ascorbate Peroxidase Reveal a Complex Mode of Interaction between Reactive Oxygen Species, Plant Development, and Response to Abiotic Stresses

Abstract: Reactive oxygen species (ROS) play a key signaling role in plants and are controlled in cells by a complex network of ROS metabolizing enzymes found in several different cellular compartments. To study how different ROS signals, generated in different cellular compartments, are integrated in cells, we generated a double mutant lacking thylakoid ascorbate peroxidase (tylapx) and cytosolic ascorbate peroxidase1 (apx1). Our analysis suggests that two different signals are generated in plants lacking cytosolic APX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
253
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 317 publications
(263 citation statements)
references
References 36 publications
10
253
0
Order By: Relevance
“…These data indicate that gun mutant screens specifically disrupted a few distinct mechanisms that downregulate the expression of PhANGs when chloroplast biogenesis is blocked, not complex metabolic situations. The findings that these mechanisms appear conserved in all plants tested [17] and contribute to stress tolerance [4,5,11,14], the circadian rhythm [7,8] and development [38][39][40][41] provide evidence that they contribute plastid-to-nucleus signalling in natural environments.…”
Section: The Gun Mutant Screenmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that gun mutant screens specifically disrupted a few distinct mechanisms that downregulate the expression of PhANGs when chloroplast biogenesis is blocked, not complex metabolic situations. The findings that these mechanisms appear conserved in all plants tested [17] and contribute to stress tolerance [4,5,11,14], the circadian rhythm [7,8] and development [38][39][40][41] provide evidence that they contribute plastid-to-nucleus signalling in natural environments.…”
Section: The Gun Mutant Screenmentioning
confidence: 99%
“…Plastidto-nucleus signalling affects numerous plastidic and extraplastidic processes, such as the biogenesis of chloroplasts and amyloplasts [3][4][5][6], the circadian rhythm [7,8], DNA replication [3], the transcription of genes that encode ribosomal RNA by RNA polymerase I [9], development [10] and the optimization of photosynthesis to various qualities of light [3]. Plastid-to-nucleus signalling also contributes to the response to wounding, biotic stress, abiotic stress and sugar [2,3,9,[11][12][13][14]. Thus, plastid-to-nucleus signalling broadly affects plant cells by optimizing chloroplast function and helping to coordinate extrachloroplastic processes with chloroplast function.…”
Section: Introductionmentioning
confidence: 99%
“…The primary function of EXECUTER2 is that of a modulator that attenuates and controls the activity of EXECUTER1 dependent upon enzymatic lipid peroxidation events (Przybyla et al, 2008). Another key component of the chloroplast-to-nucleus signaling, GUN1, that mediates ROS and/or redox responses in Arabidopsis (Arabidopsis thaliana) also has been identified recently , and its role in the plant's response to heat stress has been demonstrated (Miller et al, 2007). Lesions simulating disease resistance 1 (LSD1), the first negative regulator of plant cell death identified, seems to act as a cellular hub that keeps a positive cell death regulator, the Arabidopsis basic Leu zipper (bZIP) transcription factor AtbZIP10, outside the nucleus under oxidative stress conditions.…”
Section: Ros Signal Perception and Transductionmentioning
confidence: 99%
“…These reports strengthen the link between ROS scavenging and metabolism and demonstrate that proper regulation of ROS requires reducing power that can be supplied by photosynthesis, respiration, and/or different carbon utilization pathways. Insight into the cross talk between different ROS and ROS scavenging mechanisms was gained from studies of double or triple mutants that lack key ROS scavenging enzymes in different subcellular locations (Giacomelli et al, 2007;Miller et al, 2007) and exploration of cross talk between distinct ROS such as singlet oxygen and H 2 O 2 (Laloi et al, 2007). These studies not only exposed redundancy of the ROS scavenging network but also suggested that different antioxidant enzymes and different ROS in the same or different compartments mediate signature signals that control chloroplast function and plant response to various environmental stimuli.…”
Section: New Perspectives On Ros Scavengingmentioning
confidence: 99%
“…In particular, several studies have demonstrated that biomarkers of oxidative stress can provide satisfactory information on the response of fish to environmental stressors (Farombi et al, 2007;Miller et al, 2007;Monterio et al, 2007;Pavlović et al, 2010). Oxidative stress results from an imbalance between the formation of reactive oxygen species (ROS) and the activity of the cellular antioxidant defense system, leading to oxidative damage of cellular molecules (Kohen and Nyska, 2002).…”
Section: Introduction 1)mentioning
confidence: 99%